Implementation of singular spectrum analysis in the forecasting of seawater wave height - Utami, Wika Dianita; Agustina, Ade Candra (Desimal: Jurnal Matematika, 2023)
Indonesia is renowned as a maritime nation, positioned amidst the Pacific Ocean and the Indian Ocean. This strategic location grants Indonesia the distinct advantage of serving as a global crossroads for maritime traffic, particularly with regards to trade and waterborne transportation. Among Indonesia's bustling ports, Tanjung Priok Port stands out as one of the busiest. In this context, the measurement of seawater wave height assumes a pivotal role in shaping the dynamics of transportation and commercial activities at Tanjung Priok Port. Hence, the availability of predictive insights into forthcoming seawater wave height assumes paramount significance in proactively addressing potential calamities and orchestrating maritime endeavors more efficaciously. This study aims to apply the Singular Spectrum Analysis (SSA) technique to forecast the wave height of seawater at Tanjung Priok Port. The dataset employed encompasses the daily seawater wave height observations recorded at Tanjung Priok Harbor during the timeframe from January 2022 to May 2023. The findings of this research unveil a parameter value of L = 98, a Grouping Effect (r) of 13, and a Mean Absolute Percentage Error (MAPE) value of 10.01%. This MAPE value signifies that the forecasting yielded by the Singular Spectrum Analysis (SSA) methodology exhibits a satisfactory level of accuracy in prognosticating future seawater wave heights at Tanjung Priok Port.